OPTIMIZATION OF INCENTIVE GIVING THROUGH MULTI-CRITERIA DECISION ANALYSIS APPROACH - Helmiah, Fauriatun; Siregar, Iqbal Kamil (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Royal Kisaran, 2025)
Abstract: This research aims to optimize the provision of incentives to employees (sales team) in a company using a multi-criteria approach. Many companies face challenges in determining criteria and mechanisms for providing incentives that are effective and fair to improve work performance and motivation. The multi-criteria approach used is Multi-Attribute Utility Theory (MAUT) which can assess various aspects of employee performance comprehensively and objectively. Factors considered include productivity, quality of work, attendance, innovation and overall turnover. The research results show that the multi-criteria approach provides a more comprehensive and accurate assessment, so that companies can develop a more transparent and effective incentive system. Implementation of this approach is expected to increase employee motivation and productivity, help companies achieve their business goals more efficiently, and provide long-term benefits in the form of increased employee loyalty and competitiveness in the field.Keywords: optimization; incentives; multi criteria; maut method Abstrak: Penelitian ini bertujuan untuk mengoptimalkan pemberian insentif kepada karyawan (tim sales) di sebuah perusahaan dengan menggunakan pendekatan multikriteria. Banyak perusahaan menghadapi tantangan dalam menentukan kriteria dan mekanisme pemberian insentif yang efektif dan adil untuk meningkatkan kinerja dan motivasi kerja. Pendekatan multikriteria yang digunakan adalah Multi-Attribute Utility Theory (MAUT) dapat mengevaluasi berbagai aspek kinerja karyawan secara menyeluruh dan objektif. Faktor-faktor yang dipertimbangkan meliputi produktivitas, kualitas kerja, kehadiran, inovasi dan omset keseluruhan. Hasil penelitian menunjukkan bahwa pendekatan multikriteria memberikan penilaian yang lebih komprehensif dan akurat, sehingga perusahaan dapat mengembangkan sistem insentif yang lebih transparan dan efektif. Implementasi pendekatan ini diharapkan dapat meningkatkan motivasi dan produktivitas karyawan, membantu perusahaan mencapai tujuan bisnisnya dengan lebih efisien, serta memberikan manfaat jangka panjang berupa peningkatan loyalitas karyawan dan daya saing di lapangan.Kata kunci: optimalisasi; insentif; multi kriteria; metode maut